Settlement of Pratima Theft According to Customary and National Law in Klungkung Regency and Gianyar Regency - Made Larasati; Erikson Sihotang; Kadek Dedy Suryana (Journal Of Social Science (JoSS), 2025)
The theft of sacred objects, especially Pratima in Bali, is a pressing issue that involves legal complexities between customary and national legal systems. This problem is not only materially damaging, but also threatens the continuity of religious traditions and practices. This research aims to analyze the settlement process of Pratima theft cases from the perspectives of customary and national law, and to identify the challenges faced in integrating the two legal systems. The approach used in this research is a qualitative method with in-depth interview techniques with traditional village leaders and police investigators. The data obtained was analyzed using a thematic analysis method to identify emerging patterns and themes. The results showed that there is a mismatch between the practice of customary law and national law in the resolution of Pratima theft cases. Many cases remain unresolved due to a lack of understanding and cooperation between the two legal systems. This research concludes that a more integrative approach between customary and national law is needed to improve the effectiveness of Pratima theft case resolution. Recommendations for policy makers and law enforcers are also provided to create a more sustainable solution for the protection of Bali's cultural heritage.